2018
DOI: 10.1016/j.celrep.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Forebrain Ptf1a Is Required for Sexual Differentiation of the Brain

Abstract: The mammalian brain undergoes sexual differentiation by gonadal hormones during the perinatal critical period. However, the machinery at earlier stages has not been well studied. We found that Ptf1a is expressed in certain neuroepithelial cells and immature neurons around the third ventricle that give rise to various neurons in several hypothalamic nuclei. We show that conditional Ptf1a-deficient mice (Ptf1a cKO) exhibit abnormalities in sex-biased behaviors and reproductive organs in both sexes. Gonadal hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…The PTF1A-PRDM13 axis in Kiss1 neuron development. Previous studies showed that PRDM13 functions downstream of PTF1A, which plays distinct roles in the regulation of both the cerebellum and the hypothalamus (20,21,40). Our observations support the existence of overlapping phenotypes between Prdm13-and Ptf1a-deficient mice in the hypothalamus and cerebellum, implying that a transcriptional dysregulation in specific neuronal progenitors is the most likely pathogenic mechanism underlying the phenotypes associated with PRDM13 mutation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The PTF1A-PRDM13 axis in Kiss1 neuron development. Previous studies showed that PRDM13 functions downstream of PTF1A, which plays distinct roles in the regulation of both the cerebellum and the hypothalamus (20,21,40). Our observations support the existence of overlapping phenotypes between Prdm13-and Ptf1a-deficient mice in the hypothalamus and cerebellum, implying that a transcriptional dysregulation in specific neuronal progenitors is the most likely pathogenic mechanism underlying the phenotypes associated with PRDM13 mutation.…”
Section: Discussionsupporting
confidence: 86%
“…Recessive mutations of PTF1A are associated with pancreatic and cerebellar agenesis/hypoplasia (39). Further, PTF1A was recently found to be required for the development of the hypothalamus in the mouse, where its forebrain-specific deletion leads to disruption of the Kiss1 neuronal system, hypogonadism and altered sexual behaviours, via a mechanism that does not involve a GABAergic/glutamatergic imbalance (40). These findings suggest the possibility that PTF1A or PRDM13 mutations may be responsible for some congenital disorders characterized by both cerebellar hypoplasia and CHH.…”
Section: Introductionmentioning
confidence: 93%
“…Given the parallels between DA neurons/ coronet cells and the hypothalamus, it seems reasonable to suggest that the regulatory "cocktail" of Ptf1a and Meis might also control the development of DA neuronal cell types in vertebrates. Indeed, Ptf1a has been suggested to play a role in the specification of DA neurons in the hypothalamus in mice (Fujiyama et al 2018), while Meis TFs have been implicated in the specification of DA neurons in the olfactory bulb (Agoston et al 2014) and hypothalamus (Hook et al 2018) in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Elastase-CreERTM , Rosa26R , Rosa26-RFP and Ptf1a floxed mice were previously described 27 – 30 . By mating, we obtained Elastase-CreERTM; Ptf1a floxed / floxed ; Rosa26R or Rosa26-RFP mice (Ptf1a cKO mice) in which Ptf1a -deleted cells are detected as X-gal(+) or RFP(+) cells after tamoxifen injection.…”
Section: Methodsmentioning
confidence: 99%